Geomorphology of the southernmost longitudinal valley fault : implications for evolution of the active suture of eastern Taiwan - Shyu, J. Bruce H. (2012)
In order to understand fully the deformational patterns of the Longitudinal Valley fault system, a major structure along the eastern suture of Taiwan, we mapped geomorphic features near the southern end of the Longitudinal Valley, where many well-developed fluvial landforms record deformation along multiple strands of the fault. Our analysis shows that the Longitudinal Valley fault there comprises two major strands. The Luyeh strand, on the west, has predominantly reverse motion. The Peinan strand, on the east, has a significant left-lateral component. Between the two strands, late Quaternary fluvial sediments and surfaces exhibit progressive deformation. The Luyeh strand dies out to the north, where it steps to the east and joins the Peinan strand to become the main strand of the reverse sinistral Longitudinal Valley fault. To the south, the Luyeh strand becomes an E-W striking monocline. This suggests that the reverse motion on the Longitudinal Valley system decreases drastically at that point. The Longitudinal Valley fault system is therefore likely to terminate abruptly there and does not seem to connect to any existing structure further to the south. This abrupt structural change suggests that the development of the Longitudinal Valley suture occurs through discrete structural “jumps,” rather than by a continuous northward maturation.